Pendekatan Rational Emotive Behavior Therapy Untuk Mengatasi Mysophobia (Studi Kasus Klien “C” Eks Pasien Corona) - Bela Rahmanita; Abdur Razzaq; Neni Noviza (Social Science and Contemporary Issues Journal, 2023)
ABSTRACT: This research is entitled "REBT (Rational Emotive Behavior Therapy) Counseling Approach to Overcome Mysophobia (Case Study of Client "C" Ex-Corona Patient in Mariana Village, Banyuasin I District)". The aim of this research is to find out the description of mysophobia experienced by client "C" who is a former Covid-19 patient and what the REBT counseling approach is to overcome mysophobia in client "C". This research uses field research with a qualitative approach and case study research methods. The subject of this research is an 18 year old teenage girl with the initials "C" who is one of the victims of the Covid-19 virus and has excessive anxiety about germs and limits herself to the surrounding environment. The data collection techniques used were observation, interviews and documentation. Meanwhile, the data analysis techniques used are pattern matching, making explanations (data explanation) and time series analysis. The results of this research show that after the REBT counseling process was carried out on client "C", there were changes that occurred in client "C" psychologically, physically and behaviorally, namely that he is now more open to telling stories first and his fear of bacteria has reduced and he is also It seems that he is able to think positively about dirty objects.